Tai Chi as a preventive intervention for improving mental and physical health in non-depressed college students with high perceived stress - Sun, Jingyu; Yao, Ke; Zhao, Rongji; Li, Hanfei; Cicchella, Antonio (Frontiers in Public Health, 2025)
AimNon-depressed college students with high perceived stress represent a distinct preclinical population at elevated risk for psychological deterioration. While Tai Chi is established as a mind–body exercise for improving well-being in clinical and older populations, its targeted efficacy in this specific at-risk subgroup—particularly regarding integrated physical and mental health benefits—remains inadequately explored. This study aimed to investigate the effects of a 16-week Tai Chi program on comprehensive fitness outcomes in this population.MethodsEighty-eight non-depressed students with high perceived stress (Perceived Stress Scale scores between 38 and 56, Self-Rating Depression Scale scores below 50) were randomly assigned to a Tai Chi group (n = 47), which underwent a 16-week supervised program (3 sessions/week, 90 min/session), or a control group (n = 41) that maintained usual activities. Assessments pre- and post-intervention covered health-related physical fitness and mental health status (Perceived Stress Scale, Self-Rating Depression Scale, Pittsburgh Sleep Quality Index, Fatigue Scale-14, Hamilton Anxiety Scale, and SF-36).ResultsCompared to controls, the Tai Chi group showed significant between-group improvements in lower-limb muscular endurance (squat test), perceived stress, sleep quality, somatic anxiety, role limitations due to physical health, and social functioning (all p < 0.05). Significant enhancements were also observed in physical functioning, fatigue, and general mental health (all p < 0.05).ConclusionThe 16-week Tai Chi intervention yielded concurrent benefits in physical and mental health among non-depressed college students with high perceived stress. These findings support Tai Chi as a feasible, multi-targeted preventive strategy against stress-related morbidity in this at-risk campus population.Clinical trial registrationIdentifier ChiCTR2400089594, http://www.chictr.org.cn/index.html.